Betting on a good luck cowboy - Richardson, Sara (Romance fiction writer) (Richardson, Sara (Romance fiction writer). Star Valley novel., 2023)
A former SEAL and his best friend's widow find that the path of healing leads to forbidden feelings. For widow Tess Valdez, there are two things keeping her husband's memory alive: her daughters and the ranch he loved. And Tess has thrown herself into caring for both. But when the wild horses that roam her land are threatened, Tess seizes the opportunity to become their advocate--and finds a new purpose that is hers alone. She expects resistance from some of the locals, but what she doesn't anticipate is needing the one man she can't have by her side. No one understands Tess's pain better than SEAL Silas Beck. He lost his best friend on the battlefield, and he's spent every day since living up to the promise he'd made Jace to take care of the family he left behind. Falling for Tess was never supposed to happen, and Silas knows he should leave for both of their sakes--but he can't say no when she asks him for one last favor. Even if staying means confronting feelings they'd both rather ignore...